DC-based PV-powered home energy system - Sabry, Ahmad H. (2017)
In residential applications, energy engineers are always looking for optimal utilization of solar power to manage the energy use and reduce its impact on our economy and environment. The power source in such systems is direct current (DC) in nature, but the electricity infrastructure is still based on alternating current (AC), although most of the modern available household appliances consume DC power. Therefore, there are dissipated powers due to conversion stages to handle the solar power to the household appliances. A DC based home energy system, based on the source-load voltage matching concept, is proposed to improve system performance. In a solar charge controller, the present MPPT based systems still have losses due to the switching of their semiconductor devices producing a rise in temperature that negatively affects the overall system. A controller based on an algorithm of one time maximum power point (MPP) is proposed to mitigate those losses. The efficiency of the current traditional PV-powered system is inversely affected due to the multiple conversion stages that such a system has. Therefore, this work proposes the design and development of a wireless low power consumption prototype energy monitoring system using a novel solar-battery charge controller based on the DC voltage matching concept. For more accurate mathematical representation for the empirical outcome power data, a mathematical model based on Bode Equations and Vector Fitting algorithm has been proposed to govern the load power profile of the proposed system. The work initially investigates the feasibility of using the DC distribution system to power the locally available AC appliances, that are analyzed and evaluated individually to match the DC supply either by direct coupling or some modification. The appliances are classified according to their compatibility with the DC environment to determine the efficient operating voltage range. The algorithm of the proposed charge controller uses that voltage to be assigned as the value of the full charge voltage for the battery bank. The controller algorithm requires also the variation range of the geographical weather parameters (irradiance and temperature) to specify the MPP which is equivalent to that operating voltage at minimum weather parameters. The PV array output power is directly connected through high current parallel diodes or resistance to charge the battery bank when the battery voltage becomes lower than the calculated or full charge voltage level. By contrast, the charge controller exchanges to an auxiliary load path when the battery bank reaches its full charge value. This surplus power transfers to feed another load that might be used for ventilation to reduce the solar module temperature and add some improvements to system performance. The low power consumption wireless energy monitoring allows remote monitoring for the energy consumption of appliances and power rate quality. The system can be managed via a central computer which attains the energy data via only one remote XBee RF wireless node which is processing the sensors measurement of the system components. The proposed monitoring circuit is characterized by its low power consumption due to the lack of components and its ability to access six precise analogue channels with no additional microcontroller. The energy measurements are modelled by the new proposed mathematical equations. Simulink MATLAB is used as a simulation program to imitate the processes of the practical stages of this research. The results show great utilization of the system losses, where in some appliances, the proposed topology can achieve about 99% power efficiency as compared with the traditional one. The savings of the proposed topology can be reached to about 2696.7 Wh as compared with the traditional AC-environment one, and to about 531.6 Wh as compared with the new current partly DC-environment system. The monitoring outcome of the designed GUI proves the voltage matching concept between the PV array (as a source) and the battery/appliances (as a load), which represents a significant evidence for the considered matching concept. The disposal of the DC-AC inverter opens the horizon toward high efficiency Solar-Battery-Load system not only in the residential applications but also in general.